Linguistic ideologies in Peruvian university students regarding an indigenous, Andean language, in danger of extinction and very little spread - Sandoval Zapata, Nick Bryan (2022)
Generally, Peruvian university students do not select a native language as a second language (L2); most of them prefer to choose English. In this sense, this research aims to explore what linguistic ideologies motivate such an attitude. For this reason, eight undergraduate students from the Universidad Nacional Mayor de San Marcos (UNMSM) were interviewed about Jaqaru, an indigenous Andean language that is also in danger of extinction and is very little spread. The technique used for data collection was the semi-directed interview. The collaborators were divided into two groups: A (students of less paid professions) and B (students of better paid professions). The analysis of the data allows us to conclude that both groups share three linguistic ideologies, while group A presents an additional ideology.